Composite cardiac computed tomography angiography score for improved risk assessment in chronic coronary syndromes - Lee, Subin; Giesen, Alexander; Mouselimis, Dimitrios; Weichsel, Loris; Giannopoulos, Andreas; Nunninger, Maximilian Martin; Renker, Matthias; André, Florian; Frey, Norbert; Korosoglou, Grigorios (Scientific reports, 2025)
Agatston score, the degree of lumen narrowing categorized by CAD-RADS, high-risk atherosclerotic plaque features and pericoronary adipose tissue attenuation (PCAT) are parameters, which can be assessed non-invasively by coronary computed tomography angiography (CCTA) and aid risk stratification in patients with chronic coronary syndromes (CCS). However, few studies have so far compared the prognostic value of all those parameters together. To develop and test the prognostic value of a composite CCTA score, derived from Agatston score, CAD-RADS, high-risk plaques and PCAT in patients undergoing CCTA due to CCS. Consecutive patients with clinical indication for CCTA and available clinical follow-up of ≥ 6 months after the CCTA examination were included. (i) Agatston score, (ii) CAD-RADS, (iii) the number of plaques with at least one high-risk feature and (iv) PCAT in the proximal 4 cm of the right coronary artery (RCA) were measured, and a composite CCTA score was generated considering all four parameters. The primary endpoint encompassed all-cause mortality, myocardial infarction, and coronary revascularization (> 60 days after the CCTA scan) during follow-up. In total, 759 patients (median age 68.0 (IQR 59.0-76.0) years, 352 (46.4%) female) were included. During a median follow-up of 591.5 (IQR 505.5-686.8) days, 39 (5.1%) patients reached the primary endpoint. Cox-proportional regression demonstrated that the Agatston score, the number of high-risk plaques and CAD-RADS predicted the primary endpoint, independent of age and conventional cardiovascular risk factors. The number of high-risk plaques per patient provided the most robust prediction of the primary endpoint (HR = 2.74, 95%CI = 1.56-4.80, p < 0.001), whereas the composite CCTA score outperformed all other parameters (HR = 1.54, 95%CI = 1.19-1.98, p < 0.001). The Agatston score, CAD-RADS and high-risk plaque features may provide complementary prognostic information in patients with CCS. A composite CCTA score, derived by these imaging markers may identify high-risk individuals, who may benefit from more intensified treatment and clinical follow-up in future studies.
Gesehen am 05.09.2025